Parameter Inversion Method of Multilayered Media Based on Off-Grid Sparse CMP Model With Refined Orthogonal Matching Pursuit - Liu, Renjie; Yang, Xiaopeng; Liao, Jiancheng; Qu, Xiaodong; Yin, Peng; Fathy, Aly E. (IEEE transactions on geoscience and remote sensing, 2024)
The common middle point (CMP) ground-penetrating radar (GPR) utilizes the time-delay information under different antenna separations to realize layered inversion. However, parameter inversion of multilayered media is mostly subject to heavy computational complexity and worst estimation error in the determination of refraction positions. To address the problems, an effective parameter inversion method is proposed based on off-grid sparse CMP model with refined orthogonal matching pursuit (OMP) for multilayered parameter inversion. In the proposed method, a sparse CMP signal model with accurate reflected wave propagation modeling is developed based on a refraction approximation method. An off-grid sparse CMP model is further constructed based on second-order Taylor expansion to overcome the deviation from the grid node. Then, a refined OMP algorithm based on compressed sensing (CS) is proposed with an off-grid optimization process to achieve accurate off-grid parameter inversion. Finally, the effectiveness of the proposed method is verified by simulations and experiments.